Pengembangan Media Quiz Card Treasure Berbasis Kearifan Lokal untuk Penguatan Kecerdasan Spasial Siswa di Sekolah Dasar - Angga Setiawan; Intan Susetyo Kusumo Wardhani; Wawan Prasetyo; Diyanti Jati Pratiwi; Lataniya Fie Dzikry (Global Action and Education for Society, 2026)
This research is motivated by the low spatial intelligence of elementary school students in visualizing abstract spatial concepts within Natural and Social Sciences (IPAS) learning. The objective of this research is to develop the Quiz Card Treasure medium based on Trenggalek local wisdom that is proven valid, practical, and effective in strengthening students' spatial abilities. The method employed is Research and Development (R&D) utilizing the ADDIE development model, which comprises the Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects involved 75 fourth-grade students from three elementary schools in Trenggalek Regency. Data collection techniques included expert validation sheets, response questionnaires, and performance tests. The results indicate that the developed medium met the